Load compensation in four-wire electrical power systems - Oliveira, Luís Carlos Origa de [UNESP]; Barros Neto, Manoel C. [UNESP]; Souza, Júlio Borges de [UNESP] (IEEE, 2000)
This work describes a methodology for power factor control and correction of the unbalanced currents in four-wire electric circuits. The methodology is based on the insertion of two compensation networks, one wye-grounded neutral and another in delta, in parallel to the load. The mathematical development has been proposed in previous work [3]. In this paper, however, the methodology was adapted to accept different power factors for the system to be compensated. on the other hand, the determination of the compensation susceptances is based on the instantaneous values of the load currents. The results are obtained using the MatLab - Simulink environment.
Keywords: Reactive power compensation; Power factor; Unbalances